Relation of In‐hospital Serum Creatinine Change Patterns and Outcomes Among ST‐Segment Elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention. Issue 5 (1st February 2015) - Shacham, Yacov; Leshem‐Rubinow, Eran; Gal‐Oz, Amir; Ben‐Assa, Eyal; Steinvil, Arie; Keren, Gad; Roth, Arie; Arbel, Yaron
Abstract Background The worsening of serum creatinine (sCr) level is a frequent finding among ST‐segment elevation MI (STEMI) patients undergoing primary percutaneous coronary intervention (PCI), associated with adverse short‐term and long‐term outcomes. No information is present, however, regarding the incidence and prognostic implications associated with an improvement in sCr levels throughout hospitalization, as compared with admission levels. Hypothesis Reversible renal impairment prior to PCI is not associated with adverse outcomes. Methods We retrospectively studied 1260 STEMI patients undergoing primary PCI. The incidence of in‐hospital complications and long‐term mortality was compared between patients having stable, worsened (>0.3 mg/dL increase), or improved (>0.3 mg/dL decrease) sCr levels throughout hospitalization. Results Overall, 127 patients (10%) had worsening in sCr levels, whereas 44 (3.5%) had an improvement of sCr compared with admission levels. Patients with worsening sCR had more complications during hospitalization, higher 30‐day (13% vs 1%; P < 0.001) and up to 5‐year all‐cause mortality (28% vs 5%; P < 0.001) compared with those with stable sCR. No significant difference was found regarding complications and mortality between patients having an improvement in sCr and stable sCr. Compared with patients with stable sCr, the adjusted hazard ratio for all‐cause mortality in patients with worsened sCr was 6.68 (95% confidence interval: 2.1‐21.6, P = 0.002). Conclusions In STEMI patients undergoing primary PCI, renal impairment prior to PCI is a frequent finding. In contrast to post‐PCI sCr worsening, this entity is not associated with adverse short‐term and long‐term outcomes.